From Freud to Deleuze: the under-ways of resistance - Canavêz, Fernanda; Herzog, Regina (Paidéia (Ribeirão Preto), 2011)
This work intends to work the marginal place which resistance has occupied in the psychoanalytical field, taken as what should be overcome in favor of the good continuity of the analytical process. Counter pointing this perspective, we question if the resistance couldn't possible be understood as a space of subjective production which, as such, should be positivated by the psychoanalysis. In this way, we take up the reading Deleuze does about this subject, in order to recognize in the resistance not a movement of simply payback, but a prime affirmation that brings a real possibility of creation.